2013
DOI: 10.1161/strokeaha.111.000304
|View full text |Cite|
|
Sign up to set email alerts
|

In-Hospital Risk Prediction for Post-stroke Depression

Abstract: Background and Purpose— The timely detection of post-stroke depression is complicated by a decreasing length of hospital stay. Therefore, the Post-stroke Depression Prediction Scale was developed and validated. The Post-stroke Depression Prediction Scale is a clinical prediction model for the early identification of stroke patients at increased risk for post-stroke depression. Methods— The study included 410 consecutive stroke patients who were able to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(28 citation statements)
references
References 29 publications
(30 reference statements)
1
22
0
Order By: Relevance
“…These 379 studies with their full text were retrieved and reviewed for eligibility, and 300 were excluded because of ineligible study design and outcome measures. The 79 studies met all the criteria, and these were selected for initial inclusion; after review, a total of 36 articles (Kotila et al, 1998; Pohjasvaara et al, 1998; Aben et al, 2002, 2006; Carota et al, 2005; Tang et al, 2005, 2011; Leentjens et al, 2006; Storor and Byrne, 2006; Brodaty et al, 2007; Lee et al, 2007; Lindén et al, 2007; van de Port et al, 2007; Fuentes et al, 2009; Jimenez et al, 2009; Schepers et al, 2009; Snaphaan et al, 2009; Farner et al, 2010; Ayerbe et al, 2011; Altieri et al, 2012; de Man-van Ginkel et al, 2013; Yang et al, 2013, 2015; Zhang et al, 2013; De Ryck et al, 2014a,b; Li et al, 2014; Ahn et al, 2015; Lewin-Richter et al, 2015; Shi et al, 2015; van Mierlo et al, 2015; Koh et al, 2016; Kootker et al, 2016; Malhotra et al, 2016; Metoki et al, 2016; Tsai et al, 2016) were included in the final analysis ( Figure 1 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These 379 studies with their full text were retrieved and reviewed for eligibility, and 300 were excluded because of ineligible study design and outcome measures. The 79 studies met all the criteria, and these were selected for initial inclusion; after review, a total of 36 articles (Kotila et al, 1998; Pohjasvaara et al, 1998; Aben et al, 2002, 2006; Carota et al, 2005; Tang et al, 2005, 2011; Leentjens et al, 2006; Storor and Byrne, 2006; Brodaty et al, 2007; Lee et al, 2007; Lindén et al, 2007; van de Port et al, 2007; Fuentes et al, 2009; Jimenez et al, 2009; Schepers et al, 2009; Snaphaan et al, 2009; Farner et al, 2010; Ayerbe et al, 2011; Altieri et al, 2012; de Man-van Ginkel et al, 2013; Yang et al, 2013, 2015; Zhang et al, 2013; De Ryck et al, 2014a,b; Li et al, 2014; Ahn et al, 2015; Lewin-Richter et al, 2015; Shi et al, 2015; van Mierlo et al, 2015; Koh et al, 2016; Kootker et al, 2016; Malhotra et al, 2016; Metoki et al, 2016; Tsai et al, 2016) were included in the final analysis ( Figure 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…In recent decades, overwhelming evidence has indicated that PSD is associated with well-known risk factors such as medical history (i.e., predisposing illness and smoking) (Shi et al, 2015), a history of mental disorders (de Man-van Ginkel et al, 2013), and stroke characteristics (Jiang et al, 2014). PSD is highly prevalent among both men and women; however, it appears that PSD is more common in women than men.…”
Section: Introductionmentioning
confidence: 99%
“…Post stroke depression (PSD) is a frequent complication with approximately 30% prevalence that worsens rehabilitation outcomes and confers substantial risk for suicide [24]. Moreover, PSD in turn increased the risk of stroke recurrence [5].…”
Section: Introductionmentioning
confidence: 99%
“…Cerebral infarction is a major cause of adult-onset disability and dependency worldwide, and neuropsychiatric disorders are often associated with it. Depressive disorder, which refers to emotional disorders with main symptoms of dropped interest and depression, is one of the most common emotional disorders afflicting stroke sufferers, which impedes the rehabilitation and recovery process, jeopardizes quality of life and severely increases mortality (Berg et al, 2003;Gaete and Bogousslavsky, 2008;De Man-Van Ginkel et al, 2013). Its pathophysiological mechanism has not yet been fully elucidated and is assumed to be a multifactorial process involving biological, behavioural and social factors (Chemerinski et al, 2001;de Coster et al, 2005;Singh et al, 2000;Pedroso et al, 2015;Zhang et al, 2015).…”
Section: Introductionmentioning
confidence: 99%